Simmarketstrategy: uma ferramenta computacional para avaliação de estratégias de venda de energia elétrica em mercados com precificação por oferta - Theodoro, Edson Aparecido Rozas (2023)
After 1990s, following global trends of decarbonization, digitalization and decentralization, Brazilian electricity market has been extensively transformed. Among the new proposals is the adoption of an offer-based pricing for energy auctions, in which sellers (generators) can offer marginal operation costs freely without any auditing procedure by market operator. This work intends to propose an agent-based simulation tool, using reinforcement learning techniques (Q-learning) and Python programming language. This tool is used for energy selling strategy assessment in day-ahead markets with hourly discretization, and seeks the best selling offers in order to maximize agent’s operational profit. The proof of concept validation was conducted in a small power grid in order to: (i) gain insights about generators market power, (ii) study tacit collusion phenomena among sellers in imperfect information environments, and (iii) improve generators’ offer behavior for profit maximization.